Entrepreneurship Education In Nigerian Universities: A Tool For National Transformation - Olorundare, Adekunle Solomon; Kayode, David Jimoh (Penerbit Universiti Sains Malaysia, 2014)
Nigeria is faced with myriad of problems among which are graduate unemployment, poverty, crime, and other social vices, which are as a result of economic meltdown or unsustainable development in the country, which needs urgent attention. In order to overcome this menace, this position paper examines the nature and concept of entrepreneurship education and its application for graduates of Nigerian universities. The specific impact of entrepreneurship education on the society for national transformation among which are the provision of employment opportunities, increase in Gross Domestic Product (GDP), improved standard of living as well as under-dependency on white collar job by the universities’ graduates are discussed. The paper comes up with a model of how public and private partnership can be enhanced through entrepreneurship education in Nigerian universities towards national transformation. The challenges of entrepreneurship education which include inadequate trainers or little knowledge of entrepreneurship by the universities’ lecturers, inadequate fund for the program by the universities administrators as well as challenges in the area of curriculum development and implementation were also pointed out and recommendations were made on how such challenges can be overcome towards the practical realisation of entrepreneurship education in our higher institutions.